(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
To improve the lateral stability of car hauler way you value optimal cargo location parameters, elastically mounted on a platform, developed a mathematical model of its motion. At the same time take into account fluctuations in cargo and car hauler. According to the simulation results revealed that the system for car «hauler – cargo» accounting for elastic properties leads to a significant decrease in the frequency and amplitude of the system vertical oscillations. Therefore, the presence of the cargo can be regarded as a dynamic passive damping (in the case of a correct choice and design of layout parameters). There is proposed to reduce the distance between the cargo and the upper platform by determination of maximum values of the cargo oscillations amplitudes. In turn, the reduction of the height of the platform reduces the height of the center of gravity of the system, improves the stability of car hauler. Keywords: car hauler, dynamic processes, fluctuations, platform, stability.